GPR39 (Zinc Receptor) Knockout Mice Exhibit Depression-Like Behavior and CREB/BDNF Down-Regulation in the Hippocampus - Młyniec, Katarzyna; Budziszewska, Bogusława; Holst, Birgitte; Ostachowicz, Beata; Nowak, Gabriel (The international journal of neuropsychopharmacology, 2015)
Background:Zinc may act as a neurotransmitter in the central nervous system by activation of the GPR39 metabotropic receptors.Methods:In the present study, we investigated whether GPR39 knockout would cause depressive-like and/or anxiety-like behavior, as measured by the forced swim test, tail suspension test, and light/dark test. We also investigated whether lack of GPR39 would change levels of cAMP response element-binding protein (CREB),brain-derived neurotrophic factor (BDNF) and tropomyosin related kinase B (TrkB) protein in the hippocampus and frontal cortex of GPR39 knockout mice subjected to the forced swim test, as measured by Western-blot analysis.Results:In this study, GPR39 knockout mice showed an increased immobility time in both the forced swim test and tail suspension test, indicating depressive-like behavior and displayed anxiety-like phenotype. GPR39 knockout mice had lower CREB and BDNF levels in the hippocampus, but not in the frontal cortex, which indicates region specificity for the impaired CREB/BDNF pathway (which is important in antidepressant response) in the absence of GPR39. There were no changes in TrkB protein in either structure. In the present study, we also investigated activity in the hypothalamus-pituitary-adrenal axis under both zinc- and GPR39-deficient conditions. Zinc-deficient mice had higher serum corticosterone levels and lower glucocorticoid receptor levels in the hippocampus and frontal cortex.Conclusions:There were no changes in the GPR39 knockout mice in comparison with the wild-type control mice, which does not support a role of GPR39 in hypothalamus-pituitary-adrenal axis regulation. The results of this study indicate the involvement of the GPR39 Zn2+-sensing receptor in the pathophysiology of depression with component of anxiety.